The Influence of Marketing Communications and Quality of Service on Patient Satisfaction Participating in the National Health Insurance Registered at the Pratana Hegar Clinic, Bandung Regency." - Zahara, Rita (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The purpose of this study was to determine and analyze: (1) Marketing Communication; (2) Service Quality; (3) Patient Satisfaction; and (4) The Effect of Marketing Communication and Service Quality on Patient Satisfaction of National Health Insurance participants registered at the Pratama Hegar Clinic, both simultaneously and partially. The research method used in this research is descriptive survey and explanatory survey, the unit of analysis in this study is the patients of National Health Insurance participants registered at Pratama Hegar Clinic, Bandung Regency with a sample of 100 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that Marketing Communication at Klinik Pratama Hegar Bandung Regency turned out that most of the registered National Health Insurance participant patients gave a fairly good response; Service Quality at Klinik Pratama Hegar Bandung Regency can generally be said to be good, Patient Satisfaction is also currently considered good. Marketing Communication and Service Quality simultaneously affect the Satisfaction of National Health Insurance Participants registered at Pratama Hegar Clinic, Bandung Regency. However, partially the Service Quality value = 0.551 is more dominant in influencing patient satisfaction than Marketing Communication value = 0.340 seen from the results of data processing. Because Service Quality is more dominant in influencing Patient Satisfaction, it is the first priority in increasing Patient Satisfaction. then the Pratana Hegar Clinic, Bandung Regency is expected to improve Marketing Communication at the Pratana Hegar Clinic, Bandung Regency by including marketing training and education, so that they are able to work more competitively for the development of clinic marketing.